A Universal High‐Gain Low‐Profile All‐Dielectric Lens Design Method for Feed Antennas - Peng, Ao; Chen, Juan; Mou, Chunhui; Zhang, Lingpu; Nan, Qin (Microwave and optical technology letters, 2025)
ABSTRACT An automatic optimization design method of all‐dielectric lenses for arbitrary feed antennas is presented in this article. The lens optimization process is divided into cross‐section parameters optimization and profile parameters optimization. First, the phase of antenna radiation field is clustered using the K‐means algorithm to optimize the cross‐section parameters. Then, the simulated annealing‐particle swarm optimization algorithm (SA‐PSO) is used to further obtain the profile parameters. The optimization results for two typical feed antennas are given to verify the feasibility of proposed method. For a horn antenna in 18–26 GHz band, the maximum gain can be improved by 6.94 dBi with a minimum profile size of 1.69 λ 0 ${λ }_{0}$. For a Bow‐tie antenna operating at 0.35–0.75 GHz band, the maximum gain can be improved by 2.39 dBi with a profile of 0.055 λ 0 ${λ }_{0}$. The results show that proposed method has the properties of high gain, controllable profile, and universal applicability. It can be applied to the design of high‐gain lenses for antennas in various complex communication scenarios.